Matrix of universitary self-Assessment for Psychology career - Orellana Manrique, Oswaldo (2006)
The document constitutes the second part of an exploratory investigation. It is the proposal of a matrix for the university autoevaluación, from Faculty of Psychology University Nacional Mayor de San Marcos. One needs the character the autoevaluación, the objectives of improvement and the accreditation, asi like the phases that the process of the autoevaluación journeys, concluding with the matrix composed by twenty factors, doing a proposal of indicators and sources of verification.